Design and Implementation of a Web- Based Vessel Daily Report Information System for Optimizing Operational Efficiency and Accounting in the Shipping Industry - Rama Putra, Gustian; Fajar Ilmiyono, Agung; Rafif, Raid; Munggaran Akhmad, Dinar (J-KOMA : Jurnal Ilmu Komputer dan Aplikasi, 2025)
The rapid development of information technology has provided solutions to various operational challenges in the shipping industry, particularly in daily reporting systems that are still performed manually using spreadsheets. PT. LSM currently faces inefficiencies, data inaccuracy, and lack of real-time access in reporting vessel daily activities. To address these issues, this study aims to design and implement a Web-Based Vessel Daily Report Information System using PHP (Laravel Framework) and MySQL as the database. The research adopts the System Development Life Cycle (SDLC) methodology, which consists of planning, analysis, design, implementation, and testing phases. Data were collected through observation, interviews with company staff, and literature study. The system was designed with features such as vessel daily report management, vessel data management, inventory management, user management and automated report generation in PDF/CSV formats. The testing results, which include structural, functional and validation tests, show that the system operates in accordance with its design and successfully resolves the problems of the previous manual reporting process. The system enables real-time, accurate, and secure reporting that supports both operational monitoring and accounting-related decision-making. In conclusion, the developed system significantly improves the efficiency, accuracy and effectiveness of vessel daily reporting processes at PT. LSM. For future development, the system can be enhanced with additional features such as online crew attendance and ship requisition modules to further strengthen operational and accounting integration.